To safeguarding traditional basket making for the future - Åberg, Helena; Månsson, Sofia (FormAkademisk, 2023)
ABSTRACT Korgen lyfter [Raising Basket knowledge] is a Swedish national project started by handicraft consultants from three different regions in 2019. The project aims to promote basket making and knowledge by strengthening contemporary basket makers, make the diversity of domestic basket traditions visible and increase the interest of basket making. Through efforts in training, inventory work, seminars, lectures and networking, nationally and internationally, the project has made knowledge available and problematized the question of the fragile position of basket making. Among other things, the project has been involved in developing shorter courses in basket making and started a basket appeal related to the UNESCOs convention for the Safeguarding of the Intangible Cultural Heritage. Through a traveling exhibition, different events as well as high digital presence, the project has reached many people.